Dynamic changes in the plastid and mitochondrial genomes of the angiosperm Corydalis pauciovulata (Papaveraceae) - Seongjun Park; Boram An; SeonJoo Park (BMC Plant Biology, 2024)
Abstract Background Corydalis DC., the largest genus in the family Papaveraceae, comprises > 465 species. Complete plastid genomes (plastomes) of Corydalis show evolutionary changes, including syntenic arrangements, gene losses and duplications, and IR boundary shifts. However, little is known about the evolution of the mitochondrial genome (mitogenome) in Corydalis. Both the organelle genomes and transcriptomes are needed to better understand the relationships between the patterns of evolution in mitochondrial and plastid genomes. Results We obtained complete plastid and mitochondrial genomes from Corydalis pauciovulata using a hybrid assembly of Illumina and Oxford Nanopore Technologies reads to assess the evolutionary parallels between the organelle genomes. The mitogenome and plastome of C. pauciovulata had sizes of 675,483 bp and 185,814 bp, respectively. Three ancestral gene clusters were missing from the mitogenome, and expanded IR (46,060 bp) and miniaturized SSC (202 bp) regions were identified in the plastome. The mitogenome and plastome of C. pauciovulata contained 41 and 67 protein-coding genes, respectively; the loss of genes was a plastid-specific event. We also generated a draft genome and transcriptome for C. pauciovulata. A combination of genomic and transcriptomic data supported the functional replacement of acetyl-CoA carboxylase subunit β (accD) by intracellular transfer to the nucleus in C. pauciovulata. In contrast, our analyses suggested a concurrent loss of the NADH-plastoquinone oxidoreductase (ndh) complex in both the nuclear and plastid genomes. Finally, we performed genomic and transcriptomic analyses to characterize DNA replication, recombination, and repair (DNA-RRR) genes in C. pauciovulata as well as the transcriptomes of Liriodendron tulipifera and Nelumbo nuicifera. We obtained 25 DNA-RRR genes and identified their structure in C. pauciovulata. Pairwise comparisons of nonsynonymous (d N) and synonymous (d S) substitution rates revealed that several DNA-RRR genes in C. pauciovulata have higher d N and d S values than those in N. nuicifera. Conclusions The C. pauciovulata genomic data generated here provide a valuable resource for understanding the evolution of Corydalis organelle genomes. The first mitogenome of Papaveraceae provides an example that can be explored by other researchers sequencing the mitogenomes of related plants. Our results also provide fundamental information about DNA-RRR genes in Corydalis and their related rate variation, which elucidates the relationships between DNA-RRR genes and organelle genome stability.